Ranitidine Inhibition of Breast Tumor Growth Is B Cell Dependent and Associated With an Enhanced Antitumor Antibody Response - Rogers, Dakota; Vila-Leahey, Ava; Pessôa, Ana Clara; Oldford, Sharon; Marignani, Paola A.; Marshall, Jean S. (Frontiers in Immunology, 2018)
Background The histamine receptor 2 antagonist ranitidine is a commonly used, non-prescription, medication. It limits the development, growth, and metastasis of breast cancers in mouse models of disease. In this study, we examined the role of B cells in this response, the impact of ranitidine on the development of antitumor antibodies and subpopulations of natural killer cells using murine breast cancer models. Methods Peripheral blood granulocyte populations were assessed in both E0771-GFP and 4T1 orthotopic tumor-bearing mice by evaluation of stained blood smears. Antibody responses were assessed both in terms of the levels of anti-GFP antibodies detected by enzyme-linked immunosorbent assay and also by antibody binding to the surface of tumor cells evaluated by flow cytometry. B cell and NK cell populations were examined in the draining lymph nodes and spleens of tumor-bearing animals, by flow cytometry with and without ranitidine treatment. Results Oral ranitidine treatment was not associated with changes in peripheral blood granulocyte populations in tumor-bearing mice. However, ranitidine treatment was associated with the development of enhanced antitumor antibody responses. This was not limited to the tumor setting since ranitidine-treated mice immunized with ovalbumin also demonstrated increased IgG antibody responses. Analysis of B cell populations indicated that while B1 cell populations remained unchanged there was a significant decrease in B2 cells in the tumor-draining inguinal lymph nodes. Notably, ranitidine did not significantly inhibit primary tumor growth in B cell-deficient animals. Examination of NK cell populations revealed a significant decrease in the proportion of intermediately functionally mature NK cells populations (CD27+CD11b−) in ranitidine-treated tumor-bearing mice compared with untreated tumor-bearing controls. Conclusion These data demonstrate an important role for B cells in the enhanced antitumor immune response that occurs in response to ranitidine treatment. Our findings are consistent with a model, whereby ranitidine reduces tumor-associated immune suppression allowing for the development of more effective antitumor responses mediated by B cells which may include the participation of NK cells. These data underline the importance of considering widely used histamine receptor antagonists as modulators of antitumor immunity to breast cancer.